STRUCTURE AND PROPERTIES OF DEPOSITED COATINGS OF COMPOSITE MATERIAL OBTAINED USING THE SHS PROCESS - LUZAN, SERGII; SYTNYKOV, PAVLO (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The study presents the results of theoretical and experimental investigations on the development of composite material obtained using the method of self-propagating high-temperature synthesis (SHS process). Titanium powder Ti, carbon black C, silicon oxides SiO2 and aluminum oxides Al2O3, as well as aluminum powder AI, iron oxide Fe2O3, and thermosetting powder PT-NA-01 were used as starting materials for the modifying component. Mechanical activation of the initial charge with variation of processing parameters was carried out in a ball mill of the KM-1 model, developed by the authors of the study, of the intermittent principle of operation with a working steel drum volume of 1.5-10-4 m3. The duration of mechanical activation of the charge was 15 minutes at 130 rpm and a ratio of 1:40 of the charge mass to the mass of grinding media (steel balls with a diameter of 6 mm). Initiation of the SHS process was performed using a special device by supplying a red-hot nichrome spiral with a diameter of 0.8 mm. A self-fluxing alloy of the Ni-Cr-B-Si system, grade PG-10N-01, was used as a matrix material. The prototypes were surfaced on a 3 mm thick plate of 65G steel with a non-consumable graphite electrode with a diameter of 9.5 mm, at a current of 110 A in direct polarity. The macro- and microstructure of the coatings was studied, their X-ray diffraction analysis and scanning electron microscopy were performed, and the mechanical properties of the coatings, including their microhardness and wear resistance, were determined. Based on the studies, it was found that the introduction of a modifying component into the matrix material obtained using the SHS process allows to obtain titanium TiC and silicon SiC carbides in the coating structure, which increase the microhardness of the deposited layer and, accordingly, its wear resistance. The developed composite material can be recommended for increasing the service life of parts that work in abrasive environments.
Keywords: resource; SHS-process; charge; mechanical activation; composite material; carbide; surfacing; hardness; machine parts